PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP PROFITABILITAS PADA PERUSAHAAN INDUSTRI PENGHASIL BAHAN BAKU SEKTOR PERKEBUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013 – 2017 - Satria Rukmana, Heru; Ikhbal Saputra, Muhamad (Economicus, 2019)
The purpose of this study was to determine the effect of Corporate Social Responsibility (CSR) on company profitability. The independent variable in this study is the disclosure of Corporate Social Responsibility (CSR) as measured by indicators of the global reporting initiative (GRI) such as CSR-economy, CSR-environment, and CSR-social. The dependent variable in this study is the company's profitability measured by using net profit margin (NPM). This research is a clause study. The sampling technique was carried out using the purposive sampling method with the criteria of plantation companies listed on the Indonesia Stock Exchange which published a complete financial report for the 2013-2017 period. The data analysis technique was carried out by the method of Multiple Linear Regression using SPSS 23 program tools. The results of this study are CSR-economic disclosure has no effect on NPM, CSR-environmental disclosure has a negative effect on NPM, and CSR-social disclosure has no effect on NPM, CSR-economic disclosure, CSR-environment, CSR-social has a positive effect on NPM.